GAMBARAN TINGKAT MOTIVASI KERJA KARYAWAN PT. TOS DENGAN MENGGUNAKAN METODE EXPECTANCY THEORY - Elisabeth Lasmira Utami; Retno Triani (MANASA, 2015)
The purpose of this research is to describe the level of employee motivation PT. TOS by using the Expectancy Theory. Expectancy theory used to describe not only the levels of employee motivation but also factors forming their motivation, including expectancy, instrumental, as well as the value of the rewards given (valance). This research uses a quantitative approach with the respondents are 50 employees of PT. TOS with a minimum service of one year. They asked to complete the questionnaire of Expectancy Theory, which indicators proposed by Lunenburg. The findings showed that 10% of respondents work in a low motivation, 70% of respondents work on the moderate motivation, and 20% of respondents work in the high level of motivation (20 %). Furthermore, instrumentality was found as the lowest factor contributing to the motivation. The management needs to pay attention on the instrumentality factors in order to build a strong level of their employee motivation.